Tinjauan Qawaid Fiqhiyah Muamalah Terhadap Transaksi Dropship - Alfi Nur Khoiriyah (ITB AAS INDONESIA Surakarta, 2023)
Transactions using dropship system have been very popular since the development of digital transactions in the marketplace. So that there is no doubt or ambiguity with this transaction, it is necessary to study the legal basis of muamalah itself. Writing this article using literature study as a method of writing. There are three contracts that are used as an alternative to the permissibility of dropship transactions, namely salam, wakalah, and samsarah. The use of the contract can be used according to the conditions and capabilities of the people who do.